EVALUASI EFEKTIVITAS MEDIA KOMUNIKASI PEMASARAN DENGAN MODEL ICTRT FOR MOBILE STUDI KASUS: MARKETPLACE GODEVI: STUDI KASUS MARKETPLACE GODEVI - I Wayan Suartawan; Bernadus Bernando Bria; Ni Made Gandhi Sanjiwani (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2023)
The PSBB (Large-Scale Social Restrictions) Policy significantly impacted tourist villages in Bali, resulting in many of them only being able to bring in a limited number of visitors per year. One digital marketing platform that has been helpful to these villages is the Godevi Marketplace. The study aims to evaluate the effectiveness of the Godevi website and provide recommendations for increasing tourist engagement and traffic. Using the ICTRT model for mobile and a qualitative approach, the study surveyed 97 tourists and interviewed experts. A total of 5 variables with 51 instruments using the ICTRT model for mobile were analyzed by measuring the effectiveness of the website. The results show that the Godevi website is relatively effective, particularly in terms of destination branding. However, the website could improve in terms of relationship and transaction dimensions. The study recommends that tourism village website managers, specifically Godevi, optimize relationship features and reduce transaction obstacles.